EFEKTIVITAS IMPLEMENTASI KEBIJAKAN PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT IV DALAM MENINGKATKAN KINERJA PEJABAT STRUKTURAL ESELON-4 DI LINGKUNGAN PEMERINTAH KABUPATEN SUKABUMI - Hirawan, Wan A (2011)
The policy implementation of leadership training and education and the policy of accountability of government institution performance were the contextual policies. Competence profile to carry out the high performance duties quite needed to entry outonomy, reformation, and globalization. Learning process efectively and official government performance were the actual centre issues. Correlation of the learning process efectively toward the official government performance to be analysed as the research focus of this problem. The objectives of this research to analyse the relationship of independent variables with the learning process efectively, and lerning process efectively with the official government performance of echelon-4. The theoritical background consist of policy implementation consepts of William N Dunn, learning process consssepts of De Corte and other relevan theories. Performance measurement based on the regulation of Domestic Affairs Ministry Number 893.3/268/Sj and completed by performance background theory. Quantitative research approach used the correlational descriptive survey which consist of inductive analysis and deskriptive analysis complementary. Statistic method used the Linier regression, Product Moment correlation, Parsial correlation, and Chi-Square. The combination of questionaire, interview, observation, and library study was used to collect data and information. The inductive analysis show the learning process effectively to be determined by subject matter accuracy, using the method, trainer ability, trainee preparation, and official performance. Pearson correlation r = 0,756, R2 = 0,572, and the equation of significant multiple regression Y1 = 0,197 X2 + 0,461X3 + 0,201 X4. This result recommended that 57,20 percent of learning process effectively to be determined by those inputs variables. Higer inputs implementation would effect the more effective of learning process. The significant correlation of learning process effectively and increasing the performance results Pearson correlation r = 0,731, R2 = 0,535, and the equation of significant regression Y2= 1,481 = 0,591 Y1. This result means 53,50 of increasing the performance to be determined by learning process effectively. More effective of learning process should effect the more increased performance. The descriptive analysis show the level of learning process effectively was just being 74,74 and the level of increasing performance was just being 74,25 from the expected ideal score. Inspiring the close relationship were being recommended the application of hipotetic model of leadership training and education oriented performance. The conclusion of the study informed that the implementation of leadership training and education policy show ineffectively so that didn't effect to increase the official Government performance optimally. The improvement of inputs, process, outputs, and outcomes should be done immediately by the government and proposed to give any consideration for the aplication of leadership training and education oriented performance.